El proceso de reparación colectiva de las grandes catástrofes - Vitorelli, Edilson (2024)
This paper analyzes the case of the Brumadinho disaster, occurred in Brazil in 2019, which caused the death of 272 people, in addition to serious environmental damage. The Brazilian collective process system, formed predominantly by public institutions, responds with the prompt prosecution of collective actions, which resulted, in a period of two years, in three collective agreements. This article analyzes, through bibliographical research and primary data, the elements of the Brazilian collective litigation model that contributed to the success of the case and how they could serve as inspiration for other countries.